Model of Physical Activity (Gambo Rasa) on Type-2 Diabetes Mellitus Glucose Level in Working Area of Bolo Health Center - Abdul Haris (Journal of Global Pharma Technology, 2020)
Introduction: The principle of managing diabetes mellitus consists in setting management goals, modifying diet and exercise, medication, monitoring blood glucose levels, monitoring complications regularly, and evaluating laboratories. In addition to these principles, four main pillars of diabetes mellitus management were more concise to understand, which include education, diet, exercise, and medicine. Exercise was considered important for diabetes mellitus management because it can cause physiological effects such as lowering blood glucose levels, lowering fat levels the body, decreases blood lipid levels, lowers blood pressure, and improves fitness. Methods: The research design used was "one group pretest-posttest design", researchers examined changes that occur after an intervention. Data were analyzed using paired sample t-test. Results: The results showed that there was an influence of the physical activity model (Gambo Rasa) on blood glucose levels of type-2 diabetes mellitus. Keywords: Model of Physical Activity, Gambo Rasa; Type-2 Diabetes Mellitus; Blood Glucose